Зв’язок алгебраїчного та топологічного виводу правила Мезона - Гапон, Н. Я. (ХНУРЕ, 2025)
This work is devoted to Mason's rule that is used to reduce and simplify signal flow graphs and allow to get the gain expression. Signal flow graphs are used in the analysis of microwave devices. Signal flow graphs are associated with matrices, and linear algebra methods, such as Cramer’s rule, are used to derive Meson’s formula. The aim of this work is the comparison of algebraic and topological derivation of Mason's rule.
Keywords: правило Мезона; Mason's rule